Pembentukan Dan Pelaksanaan Posyandu Remaja Kelurahan Pattirosompe Dengan Penerapan Games Untuk Meningkatkan Minat Remaja - Burhanuddin Burhanuddin; Surya Ashari; Alfito Deanova; Rika Safitri; Dian Ramadhani; Faaizah Faaizah; Diyah Dwi Lestari R; Erviana Erviana; Muhammad Fiqram Hardinarti (Lembaga Pengembangan Kinerja Dosen, 2024)
Community service program, in collaboration with PUSKESMAS Pattirosompe. Previously, POSYANDU for teenagers in the Tomodi neighborhood had not implemented games for the implementation of POSYANDU, which resulted in every time there was an inspection, teenagers were less enthusiastic about attending. This Community Service aims to change the pattern of providing POSYANDU material to teenagers with a games system. The community service program not only changed the POSYANDU pattern but also established a youth POSYANDU in the Bulu Citta environment, starting with collecting data on teenagers covering ages 10 to 18 years. It is hoped that this service can increase teenagers' interest and insight into the importance of health. The service team has established a POSYANDU for teenagers in the Bulu Citta neighborhood, carried out health checks, provided games and counseling about teenage reproduction in the Bulu Citta and Tomodi neighborhoods.